(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the characteristics of umbilical cord blood cells and to explore some factors associated with the characteristics of umbilical cord blood cells in newborns. Subjects and methods: This cross-sectional descriptive study included 58 newborns delivered at the Department of Obstetrics and Gynecology and the Neonatal Care Unit, Hue University of Medicine and Pharmacy Hospital, from March 2024 to December 2024. Results: The male to female ratio was 1.32 to 1. Term neonates accounted for 51.7%. A low birth weight infants comprised 37.9%. The characteristics of umbilical cord blood cells in newborns were as follows: the median white blood cell count was 12.32 G/l (interquartile range: 9.44-15.18 G/l); the neutrophil count was 5.43 G/l (interquartile range: 39.44-55.01 G/l); the red blood cell count was 4.29 T/l (interquartile range: 4.07-4.49 T/l); the hemoglobin concentration was 154.00 g/l (interquartile range: 142.50-161.00 g/l); and the platelet count was 231.20 G/l (interquartile range: 172.80-281.30 G/l). Preterm newborns had significantly lower white blood cell and neutrophil counts in umbilical cord blood compared to term newborns (p < 0.05). Newborns weighing less than 2500 grams had significantly lower white blood cell and neutrophil counts compared to newborns weighing 2500 grams or more (p < 0.05). Neonates with sepsis had significantly lower white blood cell and neutrophil counts in umbilical cord blood compared to healthy neonates (p < 0.05). Newborns of mothers with anemia had significantly lower umbilical cord blood hematocrit compared to infants of healthy mothers (p < 0.05). Conclusion: Gestational age, birth weight, nutritional status, and maternal and fetal factors influence umbilical cord blood indices in newborns.